Two Extension Block Kirschner Wires’ Technique for Bony Mallet Thumb - Yutaka Mifune; Atsuyuki Inui; Fumiaki Takase; Yasuhiro Ueda; Issei Shinohara; Ryosuke Kuroda; Takeshi Kokubu (Case Reports in Orthopedics)
Mallet fingers with an avulsion fracture of the distal phalanx or rupture of the terminal tendon of the extensor mechanism is known as a common injury, while mallet thumb is very rare. In this paper, the case of a 19-year-old woman with a sprained left thumb sustained while playing basketball is presented. Plain radiographs and computed tomography revealed an avulsion fracture involving more than half of the articular surface at the base of the distal phalanx. Closed reduction and percutaneous fixation were performed using the two extension block Kirschner wires’ technique under digital block anesthesia. At 4 months postoperatively, the patient had achieved excellent results according to Crawford’s evaluation criteria and had no difficulties in working or playing basketball. Various conservative and operative treatment strategies have been reported for management of mallet thumb. We chose the two extension block Kirschner wires’ technique to minimize invasion of the extensor mechanism and nail bed and to stabilize the large fracture fragment.